Retinal fingerprints of ALS in patients: Ganglion cell apoptosis and TDP-43/p62 misplacement - Pediconi, Natalia; Gigante, Ylenia; Cama, Silvia; Pitea, Martina; Mautone, Lorenza; Ruocco, Giancarlo; Ghirga, Silvia; Di Angelantonio, Silvia (Frontiers in Aging Neuroscience, 2023)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease that involves the gradual loss of motor neuron function. Although ophthalmic deficits are not considered a classic symptom of ALS, retinal changes such as axonal degeneration, similar to those in the spinal cord, have been reported in postmortem human tissues and in animal models. Moreover, the eye provides a natural window to the brain, as the retina is considered part of the central nervous system, and neurodegenerative changes in the brain may be accompanied by structural and possibly functional changes in the neuroretina and ocular vasculature. Here we report, in the retinal ganglion cell layer of ALS patients, the presence of cytoplasmic TDP-43, increased SQSTM1/p62 aggregates, activation of the apoptotic pathway, and increased microglia density. We therefore propose to use in vivo retinal biomarkers as an additional and ALS-specific early diagnostic tool, providing an opportunity to longitudinally monitor individuals and therapies over time in a noninvasive and cost-effective manner.